2008
DOI: 10.1111/j.1750-3841.2008.00769.x
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Sensory Characteristics and Taste‐Sensor Ions of MSG Substitutes

Abstract: This study analyzed the sensory attributes of MSG substitutes to determine whether they exerted synergistic or inhibition effects on taste, and the correlation between sensory attributes (which are subjective measures) and the results of electronic-tongue analysis (which are objective measures). Descriptive and electronic-tongue analyses were conducted with 10 MSG substitutes comprising combinations of 3 commercial products, and with MSG. In the descriptive analysis, the sensory characteristics of MSG substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…When comparisons were made between YE and MSG at 0.05% and 0.1% separately, YE had a significantly higher ( P < 0.05) salty enhancement at both levels and higher umami enhancement at 0.05%. Similar results were published by Jo and Lee () who compared commercial yeast extracts and their combinations with MSG in water solutions.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…When comparisons were made between YE and MSG at 0.05% and 0.1% separately, YE had a significantly higher ( P < 0.05) salty enhancement at both levels and higher umami enhancement at 0.05%. Similar results were published by Jo and Lee () who compared commercial yeast extracts and their combinations with MSG in water solutions.…”
Section: Resultssupporting
confidence: 88%
“…Our previous study found that consumers prefer to have MSG replaced by extracts from natural sources that are rich in umami substances including mushroom extract, tomato extract, kelp extract, and yeast extract (Wang & Adhikari, ). Jo and Lee () investigated the sensory attributes of three commercial yeast extracts in water solution. Results showed that compared to MSG, yeast extracts and their combinations had significantly ( P < 0.05) higher intensities of sweet, salty, bitter, and umami tastes as well as higher intensities of beef, potato, fishy, soy sauce, and mushroom flavors, all of which separated the yeast‐based MSG alternatives from pure MSG on the principal component analysis (PCA) score plot.…”
Section: Introductionmentioning
confidence: 99%
“…[37] It can also affect the astringent taste. [23] The MSG content of sample AB was the highest. A low proportion of I + G (0.9% to 1.3%) can make the chicken seasoning more umami when it is combined with MSG.…”
Section: Msg I + G and Chloridementioning
confidence: 93%
“…To understand the relationship between the data obtained by different analysis methods, partial least squares regression (PLSR) was used to establish correlation models and a relationship between the electronic tongue data, physicochemical changes [22] , and sensory evaluation data. [23] PLSR was also used to predict the physical properties of yogurt based on the response value of the electronic tongue sensor. [24] The current study evaluated the taste contribution of the brown sugar in chicken seasoning.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the FAAs were determined with the highest concentration in sample P1 compared with the other samples, primarily due to amounts of its microbial species. [57] The amino acids, especially FAAs, are critical substances naturally present in food and are responsible for the taste, aroma, and quality of various foodstuffs. [9,58,59] The long-term ripening progress of fava pastes was extremely similar to miso [51] and produced a large number of amino acids such as Glu and Asp, which imparted pastes strong umami flavor.…”
Section: Correlation Analysismentioning
confidence: 99%